168k views
3 votes
Find (F/g)(x)
F(x) = sqrt x^2-1
g(x) sqrt x-1

Find (F/g)(x) F(x) = sqrt x^2-1 g(x) sqrt x-1-example-1

1 Answer

5 votes

Answer:

Option A. √(x + 1)

Explanation:

Data obtained from the question include:

f(x) = √(x² – 1)

g(x) = √(x – 1)

(f/g) (x) =..?

(x² – 1) => difference of two square

(x² – 1) => (x – 1)(x + 1)

f(x) = √(x² – 1)

f(x) = √(x – 1)(x + 1)

(f/g) (x) = f(x) /g(x)

f(x) = √(x – 1)(x + 1)

g(x) = √(x – 1)

(f/g) (x) = √(x – 1)(x + 1) / √(x – 1)

(f/g) (x) = √[(x – 1)(x + 1) / (x – 1)]

(f/g) (x) = √(x + 1)

User Adam Byram
by
5.3k points